Protective effect of sesaminol from Sesamum indicum Linn. against oxidative damage in PC12 cells. (28th December 2012) - Cao, Wenming; Dai, Mingjun; Wang, Xiang; Yuan, Fengjiao; Chen, Fengxiang; Zhang, Weiyun
<x xml:space="preserve">Abstract</x> Sesaminol is one component of sesame oil and has been widely used as the stabilizer to extend the storage period of food oil in China. In this study, we tried to investigate the antioxidant activity of sesaminol on rat pheochromocytoma (PC12) cells oxidative damaged by H2O2. Cell viability, LDH level and apoptosis of the PC12 cells were assayed after treatment with sesaminol for 3 h and exposure to H2O2. Furthermore, superoxide (SOD), catalase (CAT), glutathione peroxidase (GSH‐Px) and intracellular ROS were assayed after exposure of the PC12 cells to H2O2. The results showed that pre‐treatment with sesaminol prior to H2O2 exposure significantly elevated cell survival rate and SOD, CAT and GSH‐Px activity. Meanwhile, sesaminol declined the secreted LDH level, apoptosis rate and ROS level of H2O2 exposed cells. Thus, sesaminol may protect PC12 against oxidative injury. Copyright © 2012 John Wiley & Sons, Ltd.